Melacak Argumen Kesetaraan Gender dalam Kitab Uqud Al-Lujjayn - Natsir, Ahmad (Ali Muchasan, 2019)
Discourse on gender in Indonesia often refers to figures from America, Europe and Arabia, so that there are still Eurocentric or arabisentric cases. An archipelago figure in the pre-independence era, Shaykh Ibn Umar al-Jawi al-Bantani, had composed a book that reviews the rights and obligations of a husband and wife. However, instead of getting appreciation, this book actually gets a lot of criticism because of the many narratives that still discredit women, ranging from books that make men big heads to accusations as a book that is the source of domestic violence. By using the five-angle approach study Amin Abdullah the author wants to express the big idea in the form of a gender equality narrative carried by Shaykh Nawawi al-Bantani. This paper provides a conclusion in the form of gender equality carried by Shaykh Nawawi al-Bantani contained in the rights obtained by the wife from her husband and vice versa. By carrying out the association with ma'ruf Shaykh Nawawi gives an idea of ​​how the association of husband and wife in the household.